2021
DOI: 10.1021/acsanm.1c02659
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes Grown on CuO Nanoparticle-Decorated Porous Carbon Microparticles for Water Oxidation

Abstract: Efficient water splitting is limited by the sluggish oxygen evolution reaction (OER) to a large extent, which inhibits the development of sustainable energy and has attracted widespread attention. In this work, a type of microsized Cu-based metal−organic framework (MOF) of Cu-BTB has been successfully synthesized by a rapid reaction within half an hour. During the subsequent pyrolysis, a large number of N-containing carbon nanotubes (NCNTs) are grown on the entire surface of hierarchically porous MOF-derived n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…With the increase of R , the characteristic peak of Cu + showed a leftward shift, the electron binding energy increased, and more Cu 2+ was formed. These represented a fuller oxidation of the OC …”
Section: Results and Discussionmentioning
confidence: 99%
“…With the increase of R , the characteristic peak of Cu + showed a leftward shift, the electron binding energy increased, and more Cu 2+ was formed. These represented a fuller oxidation of the OC …”
Section: Results and Discussionmentioning
confidence: 99%
“…27 The N-doping level of TUNPG could reach 10.10 atom % (Figure S5), higher than other reports (Table S1), even close to the theoretical upper limit of 12.5 atom % at 1000 °C. 28 In order to demonstrate that the prepatterned cyanuric acid in melamine-cyanurate enabled the formation of TUNPG, the thermal behaviors of melamine-cyanurate (with cyanuric acid) and melamine (without cyanuric acid) with the existence of 2benzimidazolethiol were compared. Different from the pyrolysis of melamine, a sharp exothermic peak was observed during the pyrolysis of melamine-cyanurate at 440 °C (Figure 2a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…14 It was reported that graphitic N in nitrogen-doped graphene could induce nonradical PMS activation. 15 As a result, hydrothermal and calcination methods have been developed to prepare nitrogen-doped graphene with high graphitic N content. 16 However, these methods involve the preparation of a graphene oxide precursor and its reaction with different nitrogen sources, suffering from high complexity, low productivity, and low doping content.…”
Section: Introductionmentioning
confidence: 99%